Modelagem da salinidade do estuário do Serinhaém, Bahia - Brasil - Santana, Rolando González (2016)
The Serinhaém estuary is located in the south of Bahia state, about 110km from Salvador, within the limits of the Ituberá municipality, between parallels 13 ° 30 'and 14 ° 00' South latitude and meridians 38 ° 50 ' and 39 ° 40 'West longitude, ending up in the Camamu Bay. It is located on the coastal part of the Environmental Protection Area (APA acronym in portuguese) of Pratigi inside the Ecopolo III. Exist in this area a low level of development of human activities, compared with other estuaries from Brazil and over the world. At the same time, it was found a lack of environmental studies, such as salinity and tidal estuary. In this work we studied the behavior of salinity in the estuary of Serinhaém, starting from the understanding of salt exchange process between the river and the sea. The study was approached from a systemic point of view, considering the different components of physical and geographical environment, hydrology, climate, morphology, oceanography, etc., in the regional and local context in which it is inserted. It was divided into three stages; first a literature review and survey of initial data, following later by collection of salinity and tidal data during five campaigns occurred in April, July and December 2014, August and September 2015. The salinity´s samples were collected at 137 stations along the estuary, with an optical refractometer and a multiparameter device Hanna. The tide stations were placed on the docks of Ituberá and Barra Serinhaém ports, using first two rules of tide and in the second measurement, three prototypes of autonomous automatic ultrasonic digital tide gauges, constructed and electronically calibrated in the lab. Finally, we done the office works, where the results of data collected were processed and represented in a GIS environment. It was concluded that there is a difference in salinity´ seasonal behavior of the estuary, and that the presence of extreme events such as "El Niño" and "La Niña" can influence the behavior of salinity. Four elements rules the salinity of the estuary, the morphotectonic that controls the relief of the bottom; the tributaries; the tide and rainfall. The tides were classified as microtidal in December 2014 and August 2015; and as mesotidal in September 2015, due to the influence of syzygy tides during the spring equinox. The estuary was classified according to the salinity as positive; according to the flow rate, as thoroughly mixed and by the movement patterns as well blended or vertically homogeneous. These results are expected to contribute to future updates of the management plans of APA-Pratigi.